IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT THROUGH MIND MAPPING TECHNIQUE AT SMA SANTO PETRUS MEDAN - Sitindaon, Christiani Sarnauli; Simamora, Rosa Maria; Tarigan, Karisma E. (Kairos English Language Teaching Journal, 2020)
This study is about improving studentsâ€™ reading comprehension on narrative text through mind mapping technique at SMA SANTO PETRUS Medan. The theory applying is Buzanâ€™s theory of mind mapping and its method are quantitative and qualitative methods. This reseach is Classroom Action Research to apply the mind mapping technique in teaching reading. The data are collected through observations, interviews, and documentations. The qualitative data consist of the table of studentsâ€™ scores, and the quantitative data consist of diary notes, interview transcripts, documentations, and studentsâ€™ works. This research consisted of two cycles. It was conducted collaboratively with the English teacher. The subjects of this research were 36 students of class X MIA in SMA Santo Petrus Medan.Â The result of this study finds that mind mapping technique can improve the studentsâ€™ reading comprehension. It is proved by the studentsâ€™ ability in reading comprehension and the studentsâ€™ scores after the test were given. In the pre-test, the studentsâ€™mean score is 61,44. Then, in the formative test cycle 1, the studentsâ€™ mean score is 62, and in the post-test cycle 2, the studentsâ€™mean score is 72. It is conclude by the mind mapping can improve studentsâ€™ reading comprehension achievement.